2012
DOI: 10.1371/journal.pone.0035367
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Changes in the Prefrontal Cortex, Anterior Cingulate Cortex and Nucleus Accumbens of Mood Disorders Subjects That Committed Suicide

Abstract: Suicidal behaviors are frequent in mood disorders patients but only a subset of them ever complete suicide. Understanding predisposing factors for suicidal behaviors in high risk populations is of major importance for the prevention and treatment of suicidal behaviors. The objective of this project was to investigate gene expression changes associated with suicide in brains of mood disorder patients by microarrays (Affymetrix HG-U133 Plus2.0) in the dorsolateral prefrontal cortex (DLPFC: 6 Non-suicides, 15 sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 78 publications
6
52
0
Order By: Relevance
“…Only tissue from the left hemisphere (grey matter only) was used. These cortical regions are consistently implicated in depression [17][18][19][20] and are involved in higher order functioning such as decision-making, that is impaired in suicide 21 .…”
Section: Brain Samples Clinical Characterization and Group Compositionmentioning
confidence: 99%
“…Only tissue from the left hemisphere (grey matter only) was used. These cortical regions are consistently implicated in depression [17][18][19][20] and are involved in higher order functioning such as decision-making, that is impaired in suicide 21 .…”
Section: Brain Samples Clinical Characterization and Group Compositionmentioning
confidence: 99%
“…Gene expression changes associated with suicide in brains of mood disorder patients were studied by microarrays (Affymetrix HG-U133 Plus2.0) in the dorsolateral prefrontal cortex, in the anterior cingulate cortex and in nucleus accumbens [83]. Several MT-1 and MT-2 isoforms (MT-1E, MT-1F, MT-1G, MT-1H, MT-1X, and MT-2A) were down-regulated in the anterior cingulate cortex of suicide subjects compared with non-suicides, and three of them (MT-1F, MT-1G, and MT-1H) were also down-regulated in the nucleus accumbens.…”
Section: Hepatotoxicitymentioning
confidence: 99%
“…It was concluded that failed neuroprotection against stress due to decreased expression levels of MT-1 and MT-2 might be molecular risk factor for suicide [83].…”
Section: Hepatotoxicitymentioning
confidence: 99%
“…The decrease of 5-HT2A expression in the suicide group was confirmed by qPCR (data not shown). Enrichment of canonical pathways analysis using Ingenuity confirmed that the serotonin receptor signaling pathway was altered in suicide brain tissue [128]. Another gene of interest previously shown to be involved in suicide [44] and that was altered in the DLPFC was the adenylate cyclase 1 (brain) (ADCY1) gene that codes for a brain specific form of adenylate cyclase responsible of the production of the second messenger cyclic AMP, ADCY was significantly down-regulated in suicide versus non-suicide patients [129].…”
Section: Genetic Criteriamentioning
confidence: 90%
“…In order to control for possible confounding effects, demographic variables, such as diagnosis and age, and RNA quality measures (RIN and slope) were used as covariates [128].…”
Section: Genetic Criteriamentioning
confidence: 99%